Unidirectional bowtie array antenna with incision gap for digital video broadcasting_T2 base station - Bancha Luadang; Chuwong Phongcharoenpanich (My University, 2015)
This study presents a unidirectional bowtie array antenna with incision gap for a digital video broadcasting-T2 base station application. The antenna element consists of a bowtie radiator with incision gap on top of a square reflector. The element achieves a bandwidth of 82.35% for |S11| of <−10 dB, covering a frequency range of 450–1080 MHz. The antenna array comprises of four identical antenna elements mounted vertically to form an antenna array. The simulated and measured results of the antenna array show a good impedance matching for |S11| of <−10 dB along a frequency range of 450–1014 MHz (77.05%). The measured gains are 13.4–16.1 dBi along an operating frequency of 470–862 MHz with the narrow half-power beamwidth in the vertical plane of ∼15° ± 5° and the half-power beamwidth in the horizontal plane of ∼60° ± 5° for a frequency range of 470–666 MHz and 90.5° for 862 MHz. The radiation pattern is degraded at the frequency higher than 950 MHz.
Keywords: Base (topology); Antenna Design and Analysis